Polnisch-dänische Äquivalenzbeziehungen im Bereich der Vergangenheitstempora - Janikowski, Krzysztof (Folia Scandinavica Posnaniensia, 2016)
The paper attempts to present an account of the interrelations between aspect and tense in Polish and Danish sentences expressing past time meaning. The starting-point of the comparative analysis is the view that different languages do not use the same morphosyntactic means for representing a category. A grammatical category is always a mapping between particular formal means and particular meanings (or functions). With reference to Czarnecki (1998) the author distinguishes between the functional-semantic category aspectuality and the formal category aspect. According to this view there are different formal means of expressing the aspectuality: morphological, syntactic and lexical. The Polish aspect is to be defined in grammatical terms, whereas its Danish counterpart rather in lexical-semantic ones. Correspondingly, tense and aspect are very closely connected with each other in Polish.